THE IMPACT OF MEDIA PROMOTION IN PUBLIC HEALTH TOWARDS SOCIETY’S STIGMA ON HIV/AIDS SURVIVORS AT KRAJAN SUB – VILLAGE, BANJARSARI WETAN VILLAGE, DAGANGAN DISTRICT, MADIUN REGENCY - Muhammad Anwarul 'Izzat; Riska Ratnawati; Avicena Sakufa Marsanti (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2021)
The 2018 national prevalence of HIV/AIDSwas 301.959 cases. The 2016 East Java had an HIV/AIDS prevalence was 6.315 cases,the prevalence of HIV/AIDS in Madiun of 2002-2009 amounted to 343 cases. The prevalence in Dagangan was 46 cases. The HIV/AIDS cases in Dagangan was small, but peoples stigma on HIV/AIDS fall in high category, one in the BanjarsariWetan village. Therefore, the purpose of this studied to identify the impact of Public Health Promotion had on peoples stigma in HIV/AIDS sufferers. The kind of this research used experimental methods of epidemiology, and used pre-experimental design (one group pretest and posttest design). The population of this studied about 1,326 people and the numbers of samples were 171 respondents. The results of pre-test and post -test studies, means 96 respondents have dropped the stigma on HIV/AIDS sufferers from pre test to posttest scores. The result of the ties' value was 59, so there is a similar value between the pre test and the post test for those who develop the stigma on HIV/AIDS. Based on wilcoxon's test analysis, the value of p=0,000 can be concluded that a significant impact can be noted between the stigma on society's intervention and the promotion of health care for those with HIV/AIDS in pre-test and post-test values. Increased tools and information infrastructure to increase public knowledge about HIV/AIDS are urgently needed.